2016
DOI: 10.1155/2016/8094275
|View full text |Cite
|
Sign up to set email alerts
|

An Anthropometric Risk Index Based on Combining Height, Weight, Waist, and Hip Measurements

Abstract: Body mass index (BMI) can be considered an application of a power law model to express body weight independently of height. Based on the same power law principle, we previously introduced a body shape index (ABSI) to be independent of BMI and height. Here, we develop a new hip index (HI) whose normalized value is independent of height, BMI, and ABSI. Similar to BMI, HI demonstrates a U-shaped relationship to mortality in the Third National Health and Nutrition Examination Survey (NHANES III) population. We fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
120
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(134 citation statements)
references
References 66 publications
7
120
4
3
Order By: Relevance
“…18 In the study done on Turkish adults it was seen that BMI, WHR, WC and HC were significantly correlated with each other and were good predictors for cardiometabolic risk factors. 19 In the study 20 done on Tehranian adults the cut-off for WHR was 0.97 which is in close agreement with present study, the value being 0.96. In the study done on Chinese women it was found that WHR was positively associated with the risk of CHD in both younger and older women, while other indices like BMI and WC were related to CHD risk primarily among younger women.…”
Section: Discussionsupporting
confidence: 89%
“…18 In the study done on Turkish adults it was seen that BMI, WHR, WC and HC were significantly correlated with each other and were good predictors for cardiometabolic risk factors. 19 In the study 20 done on Tehranian adults the cut-off for WHR was 0.97 which is in close agreement with present study, the value being 0.96. In the study done on Chinese women it was found that WHR was positively associated with the risk of CHD in both younger and older women, while other indices like BMI and WC were related to CHD risk primarily among younger women.…”
Section: Discussionsupporting
confidence: 89%
“…For example, our study population had approximately the same HI values as the original research (100 vs 100 cm), but surprisingly the present study population had a lower HC (92 vs 99 cm), height (161 vs 166 cm) and weight (61 vs 73 kg). In addition, these z ‐scores for HI, height, BMI and ABSI were found, in both NHANES III and the Atherosclerosis Risk in Communities study, to indeed be mutually almost uncorrelated in the original research; however, in the present study, the HI z ‐score was only independent of ABSI (Table ). It is likely that the NHANES III‐derived HI should be modified for application to non‐USA populations.…”
Section: Discussionsupporting
confidence: 47%
“…In the original research, the normalized value of HI is independent of height, BMI and ABSI, and the researchers believe that HI can be understood as the HC of a given person normalized to a standard height and weight. In the original research, HI showed a U‐shaped relationship to mortality in USA populations. Nevertheless, whether the same coefficients could be used to properly standardize HC for weight and height in populations that might not have the same pattern of body size and shape is unknown, as well as the usefulness of HI for prediction of diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations